Clinical use of nicotine chewing-gum. Issue 6231 (28th June 1980) - Russell, M A; Raw, M; Jarvis, M J
Abstract : Nicotine chewing-gum has recently become available to doctors in Britain for use as an aid to giving up smoking. It produces blood nicotine concentrations similar to tobacco smoking and so relieves symptoms of nicotine withdrawal. Owing partly to the slower rate of absorption of nicotine through the buccal mucosa, however, it does not reproduce the pleasure of cigarette smoking. Indeed, in the early stages it is usually slightly aversive. Optimal use in a skill requiring practice and careful instruction. Since it is an aid rather than easy cure, its use is limited to smokers who want to stop. Earlier trials showed modest advantages over placebo, but improvements in the gum and more experience in its use suggest that long-term success rates of 40% or more can be obtained. It required little time to administer and is therefore a feasible method for busy doctors.